Pertanggungjawaban Pidana Terhadap Reseller Atas Peredaran Produk Bermerek Palsu Dalam Perspektif Ketentuan Perundang-Undangan - Maharanny, Fegita; Fardiansyah, Ahmad Irzal; Tamza, Fristia Berdian (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
A brand can be said to be an intellectual property right because there is an exclusive right granted by the state to the owner of a registered brand for a certain period of time by using the brand themselves or giving permission to another party to use it so that it is called a brand right. However, in practice, brands are often misused by the Indonesian people, especially in the economic sector by business actors, in this case resellers. The problem in this study is what form of criminal liability against resellers for the circulation of counterfeit branded products from the perspective of the Trademark Law and the Consumer Protection Law and how to overcome the circulation of counterfeit branded products. The type of research used is normative research with a statutory approach and a conceptual approach. The type of data uses secondary data through literature studies. The results of this study indicate that criminal liability against resellers for the circulation of counterfeit branded products can be imposed through Law Number 20 of 2016 concerning Trademarks and Geographical Indications which emphasizes the protection of intellectual property rights for brand owners who are harmed due to acts of brand counterfeiting.